2013
DOI: 10.1108/ijmhsc-07-2013-0026
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on the mental health of immigrants, refugees and non-status people living with HIV in Toronto

Abstract: Purpose -Canadian HIV/AIDS researchers, service providers and policy-makers are faced with new challenges of providing effective and inclusive care that meets the needs of the changing populations infected with and affected by HIV. Since 2005 immigrants and refugees from ethno-racial minority communities have comprised close to 20 percent of all new HIV infections in Canada. Anecdotes shared by PLWHAs and service providers indicated that mental health challenges faced by newcomer PLWHAs was a priority concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Additionally, those from Africa or the Caribbean, those who were less than 35, and those who were not fluent in French experienced a significantly higher degree of internalized stigma. To some extent, these findings are consistent with those of other studies conducted in Canada and other regions among MLWH, PLWH, and general populations of international migrants [47][48][49][50][51][52][53][54][55][56].…”
Section: Psychosocial Vulnerabilitiessupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, those from Africa or the Caribbean, those who were less than 35, and those who were not fluent in French experienced a significantly higher degree of internalized stigma. To some extent, these findings are consistent with those of other studies conducted in Canada and other regions among MLWH, PLWH, and general populations of international migrants [47][48][49][50][51][52][53][54][55][56].…”
Section: Psychosocial Vulnerabilitiessupporting
confidence: 91%
“…It is well recognized that migrants often experience higher levels of stigma, mental illness, and challenges with accessing, building, and maintaining social support [ 51 ]. The further burden of living with HIV can amplify these challenges [ 8 , 15 , 50 , 52 , 53 ]. For example, whereas migrants in general struggle with obtaining legal status in their new country, newly-diagnosed MLWH express heightened concern around deportation as a result of stigma, discrimination, and fear from their positive diagnosis [ 8 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the consequences of these stressors may be more profound on immigrants and refugees living with HIV/AIDS infection (IR-PLWHAs). In an exploratory study, Wong, Li, Poon, and Fung (2013) showed that IR-PLWHAs suffer economic and social marginalization, stigma and discrimination which are closely connected to their gender, race, sexualities, citizenship, HIV status, and social class.…”
Section: Studies On the Mental Health And Well-being Of Immigrants/rementioning
confidence: 99%
“…Generally, there are groups, including immigrants and refugees, that are reluctant to seek health care due to different cultural beliefs and practices. [32][33][34] In order to address the needs of such groups, the nurse needs to be well prepared and have knowledge and awareness of cross-culture conflict and should also follow culturally safe practices for that group. Indeed, intersectionality welcomes the idea of cultural claiming, where culture is seen as a defense that women from minority cultures (e.g.…”
Section: Practicementioning
confidence: 99%
“…Syrian refugee women) use against predominant cultures. [32][33][34][35] In other words, the intersection of gender, race, and cultural oppression call for a commitment to emancipatory and intersectionality-guided nursing practices that permit marginalized cultural groups to protect their cultures and identities.…”
Section: Practicementioning
confidence: 99%